2020
DOI: 10.29252/jhsme.7.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between moral intelligence and psychological safety among emergency and intensive care units nurses.

Abstract: Background and Objectives: High moral intelligence in nurses is considered a supportive factor against different pressures and is assumed to promote psychological safety. The present study aimed to investigate the relationship between moral intelligence and psychological safety of nurses in emergency and intensive care units.Methods: This descriptive-correlational study was conducted on 255 nurses working in the intensive care unit and emergency department of tertiary hospitals affiliated to Birjand University… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Also, MI as a supportive agent can improve nurses’ psychological safety and reduce work-related harm. 27 …”
Section: Discussionmentioning
confidence: 99%
“…Also, MI as a supportive agent can improve nurses’ psychological safety and reduce work-related harm. 27 …”
Section: Discussionmentioning
confidence: 99%
“…Attitudes towards spiritual care may be related not only to spiritual care competency but also to mental health of nursing staff (Taheri-Kharameh et al, 2016). A survey of over three hundred intensive care nurses revealed a significantly higher level of burnout in those with a younger age, single marital status, less work experience, lower education level, and inadequate end-of-life care experience (Kim & Yeom, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Again, Atashzadeh‐Shoorideh et al (2018) revealed that moral values are an effective factor in the formation of a sense of belonging in nursing students in Iran (Atashzadeh‐Shoorideh et al, 2017). Mahmoudirad et al (2020) found in their studies that moral intelligence improves nurses' mental health and reduces work‐related harms. Mohamadi et al (2014) found a positive and significant relationship between nurses' moral intelligence levels and their work–life quality.…”
Section: Discussionmentioning
confidence: 99%